Bibliometric Analysis of the Impact of Work-Life Balance on Mental Health in the Workplace - Erliana, Yossy Dwi; Arisanti, Ivon; Astuti, Aldiana; Indriawati, Ratna; Wilanda, Alifah (Westscience Press, 2024)
This bibliometric study investigates the academic landscape surrounding work-life balance, exploring the interrelations between work-life balance and its impacts on mental health, job satisfaction, and organizational performance. Utilizing data from major academic databases from 2000 to 2023 and employing VOSviewer for network analysis, the study maps the evolution of research themes, with a special focus on changes influenced by the COVID-19 pandemic. The findings highlight the increased emphasis on mental health issues, flexibility in work arrangements, and the critical role of workplace support. The study also identifies central researchers and thematic clusters, illustrating the dynamic interplay between work-life balance strategies and employee well-being. These insights provide a valuable foundation for developing more effective policies and interventions aimed at enhancing work-life harmony.